Discovering the ethnobotanical traditions of the island of Procida (Campania, southern Italy). (4th March 2022) - Menale, Bruno; De Castro, Olga; Di Iorio, Emanuela; Ranaldi, Mirta; Muoio, Rosa
Abstract: The aim of this paper is to study at what extent current knowledge on traditional plant uses is still alive on the island of Procida (Campania, southern Italy). Information were collected using interviews on 48 persons native or residents in the island since decades. For each recorded species, scientific name, vernacular name (when available), chorotype, parts used, folk uses, and way of preparation are described. Data was collected on a total number of 92 plant species, belonging to 87 genera and 48 families. In total, 1283 use reports have been recorded: the highest number of use reports has been documented for medicinal uses, followed by food, domestic, cosmetic and veterinary uses. Regarding medicinal uses, the majority of plants are used in the treatment of skin and gastrointestinal diseases and for general health benefits. This survey showed that the custom of using plants is still alive on the island of Procida.